2023
DOI: 10.5603/fm.a2022.0017
|View full text |Cite
|
Sign up to set email alerts
|

Morphological classification and measurement of the glenoid cavity using three-dimensional reconstruction in a Chinese population

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Likewise, Rosales-Raosales et al investigated the normal structure of the fossa gleoidalis in the Spanish population 20,36 . While Nasr el-Din and his colleagues conducted a morphometric study on the variations and shapes of the acromion and fossa glenoidalis in the Egyptian population, Chen et al revealed the parameters about the shape of the fossa glenoidalis in their study on 501 scapulae in Chinese population 17,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Rosales-Raosales et al investigated the normal structure of the fossa gleoidalis in the Spanish population 20,36 . While Nasr el-Din and his colleagues conducted a morphometric study on the variations and shapes of the acromion and fossa glenoidalis in the Egyptian population, Chen et al revealed the parameters about the shape of the fossa glenoidalis in their study on 501 scapulae in Chinese population 17,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Digital calipers were used to measure parameters for rat scapula. Literature searches were carried out for the measurements of the human scapula, and the obtained literature data was evaluated [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Methodsmentioning
confidence: 99%